EVALUASI DAN ANALISIS KESESUAIAN LAHAN PERUMAHAN UNTUK MITIGASI BENCANA (STUDI KASUS: PERUMAHAN GRAHA ISOLA) - Masri, Rina Marina; Rahman, Arif Aulia; Fachrikal, Aldi Rafi; Faridwazdi, Dzakhwaan Averrous Nur; Dalili, Galih Leo; Prayogi, Galih; Hapsari, Alya Sekar (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
BPS West Bandung Regency in 2021 recorded a population of 1,181,226 people with an annual growth rate of 1.65%, with a growth rate that continues to increase every year, the need for housing in West Bandung Regency is increasing. Therefore, KPRI Universitas Pendidikan Indoensia plans to build housing, namely Graha Isola Housing to meet housing needs in West Bandung Regency, especially in Pasirhalang Village, Ciasarua District, West Bandung Regency. Housing development requires suitable land so it is necessary to evaluate land conditions and the level of disaster vulnerability because the housing site is located in an area with the potential for landslides. The research used descriptive qualitative and quantitative methods. The data used include National Digital Elevetion Model (DEM) data, Rupa Bumi Indonesia (RBI) Map of West Bandung Regency, Soil Type, Rock Type, rainfall data, West Bandung Regency RTRW Map and other literature sources. The results showed that the land suitability at Graha Isola housing site is in accordance with the land use conditions in the field, namely non-residential land so that residential development can be carried out. And the level of landslide hazard at the housing site is in a low hazard level, so that development can be carried out. However, housing development must also be adjusted to the aspects of livable housing development criteria.